Edoxaban therapy increases treatment satisfaction and reduces utilization of healthcare resources: an analysis from the EdoxabaN vs. warfarin in subjectS UndeRgoing cardiovErsion of atrial fibrillation (ENSURE-AF) study. Issue 12 (27th June 2018) - Goette, Andreas; Kwong, Winghan J; Ezekowitz, Michael D; Banach, Maciej; Hjortshoj, Soren P; Zamoryakhin, Dmitry; Lip, Gregory Y H
Abstract: Aims: The EdoxabaN vs. warfarin in subjectS UndeRgoing cardiovErsion of atrial fibrillation (ENSURE-AF) (NCT02072434) study was a multicentre prospective, randomized, open-label, blinded-endpoint evaluation (PROBE) trial comparing edoxaban with enoxaparin/warfarin followed by warfarin alone in 2199 non-valvular atrial fibrillation patients undergoing electrical cardioversion and showed comparable rates of bleeding and thromboembolism between treatments. This prespecified ancillary analysis investigated the impact of edoxaban therapy on treatment satisfaction and utilization of healthcare services. Methods and results: The Perception of Anticoagulant Treatment Questionnaire (PACT-Q2) was completed by study patients on Day 28 post-cardioversion. Higher scores represent greater satisfaction. Healthcare resource utilizations were collected from randomization to Day 28 post-cardioversion. Data from patients who received at least one dose of study drugs were analysed. Patients treated with edoxaban were more satisfied than enoxaparin/warfarin in both PACT-Q treatment satisfaction and convenience scores ( P  <   0.001 for both). Differences in treatment satisfaction scores were greater in patients who underwent non-transoesophageal echocardiography (TOE)-guided cardioversion than in patients who underwent TOE-guided cardioversion. Edoxaban was associated with fewer clinic visits (4.75 visits vs. 7.60 visits; P  <   0.001) and fewer hospital days (3.43 days vs. 5.41 days; P  <   0.05). Rates of hospitalizations and emergency room visits were not significantly different. Overall, edoxaban therapy was estimated to reduce healthcare costs by €107.73, €437.92, €336.75, and $246.32 per patient in German, Spanish, Italian, and US settings, respectively. Conclusions: The convenience of edoxaban therapy over warfarin in patients undergoing cardioversion may provide greater treatment satisfaction and cost savings to the healthcare system.